Controlling Oxygen Reduction Reaction Activities of Ag@Pt Core–Shell Nanoparticles Via Tuning of Ag in the Surface Layer. Issue 4 (6th April 2023) - Aksoy, Dilan; Karakaya, Cüneyt; Balkan, Timuçin; Savaci, Umut; Turan, Servet; Metin, Önder; Kaya, Sarp
Abstract : Pt layer thickness in Ag@Pt core‐shell nanoparticles prepared via the seeded‐growth method can be controlled in the synthesis stage. However, their oxygen reduction reaction (ORR) activity is not solely dependent on the Pt overlayer. Ag is present in the Pt shell and the ORR kinetics are facilitated by increasing the Pt shell thickness with a lessened Ag amount on the surface. More details can be found in article number 2201167, Önder Metin, Sarp Kaya, and co‐workers.